2020
DOI: 10.1016/j.ijid.2020.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Was school closure effective in mitigating coronavirus disease 2019 (COVID-19)? Time series analysis using Bayesian inference

Abstract: Highlights The effectiveness of school closure to mitigate the epidemic of COVID-19 remains unknown. Time series analyses were conducted using the Bayesian method to evaluate the effectiveness of school closure in Japan. The intervention of school closure did not appear to decrease the incidence of coronavirus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 6 publications
2
38
0
Order By: Relevance
“…A descriptive paper on school reopenings found that openings in Denmark and Norway were not associated with increased community transmission (Stage et al, 2020). Iwata et al, 2020). 11 One of the quasi-experimental studies on re-openings in Germany also examined school closures and found that they were not associated with significant decreases in transmission among children or adults (von Bismarck-Osten et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A descriptive paper on school reopenings found that openings in Denmark and Norway were not associated with increased community transmission (Stage et al, 2020). Iwata et al, 2020). 11 One of the quasi-experimental studies on re-openings in Germany also examined school closures and found that they were not associated with significant decreases in transmission among children or adults (von Bismarck-Osten et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies examining the effects of closures across multiple countries found that closure was among the most effective mitigation strategies for reducing COVID-19 spread (Haug et al, 2020;. By contrast, another multiple-country study found that school closure was the least effective mitigation strategy (Banholzer et al, 2020), and observational studies in Australia and Japan also found that school closures did not appear to reduce incidence of covid-19 (Chang et al, 2020;Iwata et al, 2020). 12 For more detail on this tracker, see https://covidschooldashboard.com.…”
Section: Introductionmentioning
confidence: 99%
“…Closing schools turned to be among the first interventions in many countries (4), presumably because of governmental pandemic plans prepared tailored to influenza. This issue, causing quarrels already 100 years back during the Spanish influenza pandemic, still persists and studies of COVID-19 can also be divided into those that claim relatively small effect (8, 14, 21) and those that rank closing schools among the most important interventions (4, and references therein). We do not follow this line of inquiry, mainly because it makes no sense to single out this specific intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The scenario R5 is inspired by a highly discussed issue of whether leave schools open or rather close them (4,21,14).…”
Section: Retrospective Analysismentioning
confidence: 99%
See 1 more Smart Citation